Bảng tổng hợp, tiếp thu, giải trình ý kiến đối với dự thảo Luật Giao dịch điện tử (sửa đổi) - Chính phủ (2022)
Toàn văn Bảng tổng hợp, tiếp thu, giải trình ý kiến đối với dự thảo Luật Giao dịch điện tử (sửa đổi)